The Molecular Detection of Leptospira spp. in Domestic Cats from Small Animal Hospital, Chiang Mai, Thailand. - Prachasilchai, Worapat; Sodarat, Chollada; Piyarangsri, Kakanang (Journal of Mahanakorn Veterinary Medicine, 2023)
Domestic cats can transmit Leptospira spp. and may play an important role in human infection. The aim of this study was to detect Leptospiral infection in mature cats presented to Small Animal Veterinary, Chiang Mai University, by using immunofluorescence assay (IFA) and real-time PCR (RT-PCR) techniques. Eighty mature cat serum and urine were collected. The results showed that all of IFA’s serological results were negative. Otherwise, we found 2.5 percent of outdoor cats (2/80) positive with RT-PCR, with one cat positive in urine and another positive in urine and serum from the Muang and Doi Tao areas, respectively. This study discovered the presence of Leptospira spp. in mature cats brought to Small Animal Veterinary, Chiang Mai University, implying that outdoor cats could be an important reservoir for the transmission of Leptospira bacteria. Furthermore, more research is needed to investigate the role of transmission in the cat and to examine the disease prevention rule not only for the owner but also for staffs in animal hospitals.